Thoraco-abdominal biomechanical model and dual-layer control method for soft robotic system with application to respiratory assistance - Zhi, Wenzhuo; Zhao, Wei; Zhang, Yan; Shi, Enming; Zhou, Yangfan; Zhang, Bi (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionRespiratory dysfunction remains a critical challenge for patients transitioning from intensive care. However, existing assistive devices often fail to address both human-robot dynamic synchronization and patient safety due to the lack of interaction force control. Therefore, this study proposes a human-robot force interaction control strategy by integrating a flexible force sensor, aimed at achieving precise alignment between assistive forces and natural respiratory rhythms.MethodsIn this study, a wearable respiratory assistive robotic system was developed to provide respiratory assistance by applying compressive force to the user’s abdomen through soft origami actuators. A thoracoabdominal biomechanical transmission analysis was conducted to reveal the cross-domain force transfer mechanisms. To improve the human-robot adaptability, a dual-layer control architecture for force-pressure coordinated control was designed. Besides, through hardware integration and system building, along with the implementation of interaction force control, the respiratory assistive robot achieves effective respiratory assistance control.ResultsWithin the 12–40 breaths/min effective respiratory rate range, PEF, MTV, and MV improved significantly. PEF had a 20.12% average increase, MTV a 19.69% average boost, and MV a 15.5% average rise. Statistically, PEF and MV improvements were highly significant across this range, while MTV was highly significant at 20 breaths/min. Respiratory MV measurements segmented by phase showed that the robot enhanced expiratory function and improved inspiratory function at certain rates within 12–40 breaths/min.DiscussionThe proposed human-robot interaction control system integrates hardware and control systems. Tests on healthy subjects in the effective operating range show that the robotic system can enhance subjects' overall respiratory function and ventilation function, offering a technical reference for future respiratory-assist robot development.